Analisis Bahaya dan Resiko Bencana Gunungapi Papandayan (Studi Kasus: Kecamatan Cisurupan, Kabupaten Garut) - Saut Aritua Hasiholan Sagala; Hadian Idhar Yasaditama (Universitas Muhammadiyah Surakarta, 2012)
Risk assessment is an important step to be carried out for disaster management. It provides information for decision makers and communities in pre-disaster, during disaster and post disaster event. Nevertheless, risk assessment in Indonesia, especially on active volcanoes is still limited. This paper presents the risk assessment of Mt. Papandayan (2.665 m), the most active volcano in West Java. The unit of analysis in this study follows the administrative boundaries of village so that the identification can be applied at village level using GIS. Hazard analysis refers to the official hazard map produced by PVMBG while the vulnerability analysis is carried out in 3 sub-analysis, physical vulnerability (7 indicators), social vulnerability (7 indicators), and economic vulnerability. The hazard and vulnerability were overlayed in order to produce the risk which is subsequently made into risk map. The findings indicate that the villages located near and on the direction of the crater have relatively higher risk compared to other villages. The risk map can be incorporated as one of references for spatial planning that integrates disaster mitigation.